High-efficiency graphene / wide-bandgap semiconductor heterojunction solar cells

By using hydrothermal synthesis technology on the zinc foil substrate to form aligned zinc oxide nanowire cores and depositing reduced graphene oxide shells, the existing solar cell technology has solved the problem of reduced efficiency and high manufacturing cost at high temperatures, and achieved efficient and economical solar cell manufacturing.

CN114402444BActive Publication Date: 2025-04-25DIMEROND TECH LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080054924.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-20
Filing Date
2020-06-02
Publication Date
2025-04-25
Estimated Expiration
2040-06-02

AI Technical Summary

Technical Problem

The existing solar cell technology has reduced efficiency at high temperatures and is highly manufactured, making it difficult to achieve high conversion efficiency and economical large-scale manufacturing.

Method used

A hydrothermal synthesis process is used to form an aligned zinc oxide nanowire core on the zinc foil substrate, and a reduced graphene oxide shell is deposited thereon. The surface defects of the nanowire core are reduced by annealing to form an efficient photovoltaic junction.

Benefits of technology

Maintaining efficient solar energy conversion at high temperatures is achieved, and manufacturing costs are reduced, significantly improving the conversion efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114402444B_ABST
    Figure CN114402444B_ABST
Patent Text Reader

Abstract

A photovoltaic solar cell device is described herein that combines the advantages of several discoveries that solve the previously unsolved problem of manufacturing high conversion efficiency solar cells at low cost. The solar cell design and basic principles disclosed herein can be applied to any type of photovoltaic solar energy application, such as large-scale photovoltaic solar power plants, rooftop solar panels, solar-powered electronic devices, and many other applications.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application No. 62 / 856,698, filed on June 3, 2019, U.S. Provisional Application No. 62 / 924,805, filed on October 23, 2019, and U.S. Provisional Application No. 62 / 937,938, filed on November 20, 2019, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present application relates generally to generating electricity using solar energy. Background Art

[0004] Various modalities of solar energy conversion are used in the art. For example, existing systems employ photovoltaic junctions to support the direct conversion of sunlight into electrical energy. It is also known to convert sunlight into heat and then use that heat to generate electricity. For example, conversion efficiencies vary between different modalities, with many hypothetical modalities performing poorly, with none achieving high conversion efficiencies. These relative conversion efficiencies, in turn, have a very direct impact on the return on investment that a business can expect to obtain from pursuing a given solar energy conversion system.

[0005] Photovoltaic power generation currently exceeds 600 gigawatts worldwide and is growing exponentially and will reach 1 terawatt within two to three years. Solar cells are made of semiconductor materials, usually silicon in crystalline solar cells. Traditionally, solar cells have two layers: an n-type with a high electron concentration and a p-type with a relatively low electron concentration. One side of the solar cell is "doped" with a p-type material such as boron and the other side is doped with an n-type material such as phosphorus, forming a single pn junction. When sunlight strikes the n-type layer, electrons are expelled from the n-region and flow through the circuit to the p-region, generating an electric current that can be captured and used to provide power. Although nonequilibrium thermodynamic theory predicts that solar cell conversion efficiencies could potentially be as high as 86%, actually achieving higher efficiencies presents difficult technical challenges, and solar cells approaching this efficiency are currently unavailable.

[0006] Most solar cells currently in commercial production are based on this single pn junction architecture of doped silicon wafers (monocrystalline or multicrystalline). The spectrum of the sun is close to the blackbody spectrum of 5800K. Most of the solar radiation reaching the earth consists of photons with energies greater than the 1V bandgap of silicon, which represents the minimum energy required to excite electrons to a state where they can participate in conduction. These photons are absorbed by silicon, but their excess energy is converted into heat rather than electricity. On the other hand, most of the solar radiation consists of photons in the infrared region of the solar spectrum, which have energies below the bandgap of silicon. These cannot be absorbed by silicon, thus further reducing the conversion efficiency of silicon solar cells. Due to these limitations, current solar cells composed mainly of silicon typically convert only about 15% to 20% of the energy in sunlight into electricity. Silicon solar panels also lose efficiency at high temperatures. Heterojunction solar cells consisting of crystalline silicon cells sandwiched between two layers of amorphous thin-film silicon have been developed. The additional layers allow more sunlight to be absorbed, thereby achieving efficiencies of 21% or slightly higher.

[0007] A lot of effort has been put into developing solar cells other than silicon that can overcome the above-mentioned drawbacks. For example, multi-junction solar cells have the potential to achieve conversion efficiencies of about 45%, according to reports. Such multi-junction solar cells are not made using silicon as the semiconductor. Instead, materials like indium gallium phosphide, indium gallium arsenide, and germanium are used to create separate semiconductor layers that respond to different wavelengths of incident sunlight, making them more efficient at converting sunlight into electricity than single-junction cells. Although they have the potential to be several times more efficient than conventional solar cells, the design is complex and difficult to manufacture, and high manufacturing costs have so far prevented them from being used for large-scale commercialization, such as rooftop or solar power plant applications.

[0008] Another prior approach, derived from prior work by the inventors and disclosed in U.S. Pat. Nos. 8,586,999, 8,829,331, and 9,040,395, envisions arrays of nanowires comprising a core of a wide bandgap material coated with a thin graphene shell grown on a foil substrate and arranged so that their longitudinal axes are substantially coaxial and parallel to the intended light beam. These patents posit that the nanostructured radial coaxial shell / core nanowire configuration enhances solar energy conversion efficiency over conventional planar solar cell configurations due to the strong light absorption properties of graphene and the much shorter electron diffusion lengths. Techniques for growing titanium oxide or silicon carbide nanowire cores are also disclosed, as well as methods for coating such nanowires by high temperature treatment of silicon carbide nanowires or by chemical vapor deposition using a methane environment. These patents report an expected cell voltage of about 1 V for the disclosed silicon carbide / graphene photovoltaic junction solar cells at standard sunlight intensities, which is only slightly higher than the voltage of conventional silicon solar cells. Because graphene-based photovoltaic junctions can be expected to maintain photovoltaic functionality at useful energy conversion levels at high temperatures that are not suitable for operation of photovoltaic devices employing silicon or other materials such as gallium arsenide, these patents focus on cogeneration applications where such cells are deployed near a second, high-temperature second mode of solar energy conversion.

[0009] The graphene-coated nanowire core-based solar cell technology disclosed in the previously cited patents does not fully address the needs of the large potential market for single-modal photovoltaic solar power generation, such as in photovoltaic solar power plants and rooftop solar panels. To overcome the shortcomings of conventional silicon-based solar cell technology in these applications, higher conversion efficiencies are needed, as well as cost-effective manufacturing processes using readily available materials. Therefore, the invention of affordable solar cells that have conversion efficiencies significantly higher than those provided by current technology and that can be economically mass-produced would significantly reduce solar power costs and promote technological solutions to the harmful environmental impacts resulting from over-reliance on fossil fuel energy. Summary of the invention

[0010] According to one aspect of the present invention, there is provided a method for forming a solar cell, comprising: providing a lower copper foil having a top surface and a bottom surface; providing a zinc foil having a top surface and a bottom surface, the bottom surface of the zinc foil being in contact with the top surface of the copper foil through at least a portion of the bottom surface area of ​​the zinc foil to form a foil substrate; forming a plurality of nanowire cores on the top surface of the zinc foil using a hydrothermal synthesis process, the nanowire cores comprising zinc oxide, wherein at least a majority of the nanowire cores are substantially aligned with each other and extend approximately perpendicularly to the zinc foil and are electrically connected to the foil substrate at a first end of the nanowire cores, the hydrothermal synthesis process forming a substantially continuous coating of zinc oxide between the zinc oxide nanowire cores; treating the nanowire cores in a post-growth annealing process to reduce structural defects at the surface of the nanowire cores; and then depositing a graphene material on at least a portion of the nanowire cores to form a plurality of shells, wherein the graphene material comprises reduced graphene oxide; wherein a second conductive electrode is connected to the plurality of shells at a second end of the nanowire core and comprises at least one metal that effectively reduces the work function of the graphene.

[0011] According to one aspect of the invention, a substantially continuous coating of non-conductive material is formed on the foil substrate, the coating comprising zinc oxide.

[0012] According to one aspect of the invention, each reduced graphene oxide shell of the plurality of shells is conformally disposed around a majority of a corresponding nanowire core.

[0013] According to one aspect of the present invention, when using 1KW / m 2 When irradiated with AM 1.5G illumination, the solar cell has an open circuit voltage between 1.5V and 3.6V.

[0014] According to one aspect of the present invention, the foil substrate further comprises at least one of titanium, brass, or steel.

[0015] According to one aspect of the invention, the foil substrate consists essentially of zinc.

[0016] According to one aspect of the invention, the plurality of nanowire cores comprises surface annealed nanowire cores.

[0017] According to one aspect of the present invention, the method further includes: forming a first conductive electrode electrically connected to the foil substrate, wherein the first conductive electrode is not electrically connected to the reduced graphene oxide shell at the first end of the nanowire core, and the second conductive electrode is not electrically connected to the nanowire core via the reduced graphene shell.

[0018] According to one aspect of the invention, the plurality of shells comprises, at least in most part, two to ten layers of reduced graphene oxide.

[0019] According to one aspect of the present invention, the plurality of shells comprises, at least in most part, two to five layers of reduced graphene oxide.

[0020] According to one aspect of the invention, the plurality of shells comprises, at least over a majority, a layer of graphene.

[0021] According to one aspect of the invention, the plurality of shells are arranged such that their longitudinal axes are oriented at least substantially parallel to each other.

[0022] According to one aspect of the present invention, the length of the plurality of shells is in the range of 5 micrometers to 25 micrometers.

[0023] According to one aspect of the present invention, the diameter of the nanowire cores in the plurality of nanowire cores does not exceed 500 nanometers.

[0024] According to one aspect of the invention, the plurality of shells are characterized by an aspect ratio of 10-250.

[0025] According to one aspect of the invention, the plurality of shells is characterized by a spatial density of 10% to 80%.

[0026] According to one aspect of the invention, the nanowire core comprises a dopant along at least a portion of its longitudinal surface.

[0027] According to one aspect of the present invention, the dopant includes at least one of aluminum, indium, chlorine and gallium.

[0028] According to one aspect of the present invention, the reduced graphene shell includes an n-type dopant.

[0029] According to one aspect of the present invention, the n-type dopant includes nitrogen.

[0030] According to one aspect of the present invention, the n-type dopant is included in the plurality of shells in an amount effective to reduce a work function of the reduced graphene oxide by at least 0.5 V.

[0031] According to one aspect of the invention, the second conductive electrode is at least partially transparent to sunlight.

[0032] According to one aspect of the present invention, the second conductive electrode is a conductive inorganic material.

[0033] According to one aspect of the present invention, the second conductive electrode is a conductive organic material.

[0034] According to one aspect of the present invention, the second conductive electrode includes at least one of indium tin oxide or graphene.

[0035] According to one aspect of the present invention, the second conductive electrode comprises reduced graphene oxide.

[0036] According to one aspect of the present invention, a substance effective to reduce the work function of the reduced graphene oxide is in contact with the reduced graphene oxide shell.

[0037] According to one aspect of the present invention, when using 1KW / m 2 When irradiated with AM 1.5G radiation, the solar cell has at least 1 mA / cm 2 short-circuit current density.

[0038] According to one aspect of the present invention, the at least one metal effective to reduce the work function of the reduced graphene oxide comprises one or more of silver, aluminum and copper.

[0039] According to one aspect of the invention, the second conductive electrode is at least partially transparent to sunlight and comprises particles of at least one metal effective to reduce the work function of the reduced graphene oxide.

[0040] According to one aspect of the invention, the material forming the second conductive electrode is dispersed between the nanowire cores.

[0041] According to one aspect of the present invention, the second conductive electrode comprises indium tin oxide containing silver particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The above needs are at least partially met by an apparatus pertaining to a high efficiency solar cell having a nanowire core of wide bandgap material and a graphene exterior, which is described in the following detailed description, particularly when studied in conjunction with the accompanying drawings, in which:

[0043] Figure 1 is a perspective view of a portion of a photovoltaic solar cell having a plurality of nanowires;

[0044] Figure 1A Yes Figure 1 A perspective view of one nanowire coated with a shell is shown;

[0045] Figure 2 is a cross-sectional diagram of a form of photovoltaic solar cell;

[0046] Figure 3 is a cross-sectional view of another form of a photovoltaic solar cell having a masking layer;

[0047] Figure 4 is a cross-sectional view of another form of a photovoltaic solar cell having a multi-component electrode;

[0048] Figure 5 It is a top view of a form of photovoltaic solar cell;

[0049] Figure 6is a scanning electron microscope image of a ZnO nanowire core grown on a foil substrate;

[0050] Figure 7 is a scanning electron microscope image of a ZnO nanowire core coated with reduced graphene oxide;

[0051] Figure 8 is a scanning electron microscope image of a ZnO nanowire core coated with graphene using polycyclic aromatic hydrocarbons;

[0052] Fig. 9 is the Raman spectrum result of ZnO nanowire core coated with reduced graphene oxide;

[0053] Fig.10 is the Raman spectroscopy result of ZnO nanowire core coated with graphene using PAH;

[0054] Fig.11 is a current-voltage plot of a photovoltaic solar cell having a ZnO nanowire core coated with reduced graphene oxide and using a silver electrode in contact with the reduced graphene oxide;

[0055] Fig.12 is a current-voltage diagram of a photovoltaic solar cell having a ZnO nanowire core coated with graphene from polycyclic aromatic hydrocarbons and using an indium tin oxide electrode in contact with the graphene;

[0056] Fig.13 is a current-voltage plot of a photovoltaic solar cell having a ZnO nanowire core coated with graphene from polycyclic aromatic hydrocarbons and using silver electrodes in contact with the graphene;

[0057] Fig.14 is a current-voltage graph of a photovoltaic solar cell having a ZnO nanowire core coated with graphene from polycyclic aromatic hydrocarbons and using electrodes comprising silver and indium tin oxide in contact with the graphene;

[0058] Fig.15 is a graph showing the results of annealing in an oxygen environment on the sheet resistance of ZnO nanowires;

[0059] Fig.16 is a graph of normalized current-irradiation wavelength, showing the wavelength independence of graphene light absorption coefficient;

[0060] Fig.17 is a graph of photocurrent for a photovoltaic solar cell having a ZnO nanowire core coated with graphene versus two light intensities differing by three orders of magnitude; and

[0061] Fig.18is a scanning electron microscope image of a ZnO nanowire core grown on a foil substrate, showing directional growth and "flower" type growth.

[0062] For simplicity and clarity, elements are illustrated in the figures, but not necessarily drawn to scale. For example, the size and / or relative position of some elements in the figure may be exaggerated relative to other elements to help improve the understanding of various embodiments of the present invention. In addition, common but well-understood elements that are useful or necessary in commercially feasible embodiments are often not depicted, so as to facilitate the less obstructed observation of these different embodiments of the present invention. Certain actions and / or steps can be described or depicted in a specific order of occurrence, and those skilled in the art will understand that this specificity about sequence is not actually required. The terms and expressions used herein have the common technical meanings given to these terms and expressions by those skilled in the art as described above, unless different specific meanings are set forth in addition herein. DETAILED DESCRIPTION

[0063] A photovoltaic solar cell device is described herein that combines the advantages of several discoveries that solve the previously unsolved problem of manufacturing high conversion efficiency solar cells at low cost. The solar cell design and underlying principles disclosed herein can be applied to any type of photovoltaic solar energy application, such as large-scale photovoltaic solar power plants, rooftop solar panels, solar-powered electronic devices, solar satellites, outdoor lighting, and many other applications.

[0064] The photovoltaic effect produces electrical energy in watts, which is the product of current and voltage. The higher the current x voltage product, the higher the cell conversion efficiency. Energy conversion efficiency is measured by dividing the output electrical power by the incident light power. Factors that affect the output include spectral distribution, spatial distribution of power, temperature, and resistive load. IEC standard 61215 is used to compare the performance of cells at ground temperature: irradiance is 1kW / m2. Specifically, a spectral distribution close to the spectral distribution of solar radiation through AM (air mass), i.e. 1.5, is used, and a cell temperature of 25°C is used.

[0065] The magnitude of the cell current depends primarily on the light absorption properties of the cell material and the intensity of the illumination. On the other hand, the measured cell voltage is primarily due to differences in the so-called "quasi-Fermi levels" of the majority charge carriers. In this regard, the work function of a material is the minimum thermodynamic energy required to migrate an electron from a solid to a vacuum point just outside the solid surface. The work function can be measured experimentally and can be shown to be directly related to the Fermi level of the majority carriers. The measured cell voltage is attributed to the effective work function of the solar cell, i.e., the difference in the "work functions" of the materials that make up the photovoltaic junction of the solar cell.

[0066] Based on in-depth and long-term research on the principles of photovoltaic science, the applicant has gained new insights, which have led the applicant to conclude that high conversion efficiency solar cells should absorb the total sunlight spectrum to provide a considerable short-circuit current, while the constituent materials can exhibit large differences in work function, thereby providing a large open circuit potential. The cell materials should also allow effective charge separation at the heterojunction, which lays the foundation for solar cells with conversion efficiencies several times higher than the prior art. Although these conclusions are far from self-evident, they are not a panacea in themselves, because the selection of materials constituting such cells and the elucidation of economic methods for manufacturing such cells pose huge challenges, and their solutions are not at all obvious. The solar cell devices disclosed herein are composed of materials selected in a manner that provides a large photocurrent at a high photovoltage, and have a conversion efficiency three times or more that of currently available solar cells. The structure and performance of these new cells, as well as the manufacturing techniques required for their effective operation, are described in detail herein.

[0067] In one aspect, the device can include, at least in part, a foil substrate on which a plurality of coated nanowire cores are disposed. The nanowire cores (e.g., including zinc oxide) can exhibit a large work function difference relative to the work function of the graphene or reduced graphene oxide shells, thereby being able to provide a large open circuit potential. In order to promote charge separation at the graphene-based photovoltaic junction, a substantially continuous coating of a non-conductive material, such as an insulator, is formed on the foil substrate between the nanowire cores. A first conductive electrode is electrically connected to the foil substrate to provide an electrical path to facilitate electron movement away from the nanowire cores, and a second conductive electrode connected to the shell at a second end of the nanowire core / shell structure provides an electrical path to facilitate positive charge movement away from the shell.

[0068] In another aspect, the photovoltaic solar cell device of the present invention is prepared by a method that forms a plurality of nanowire cores (such as nanowire cores of zinc oxide) on a foil substrate using a hydrothermal synthesis process. In some methods, at least most of the nanowire cores are substantially aligned with each other and are approximately perpendicular to the foil substrate. In one form, the hydrothermal synthesis process forms a substantially continuous insulator coating such as a non-conductive zinc oxide material on the foil substrate between the nanowire cores. The nanowire cores so formed can be subjected to a post-growth annealing process to reduce structural defects at the surface of the nanowire cores, which can effectively improve the diode properties of the nanowire array while also reducing its resistance.

[0069] In other aspects, an efficient and effective method for coating a graphene-based material around a portion of a corresponding nanowire core to form a photovoltaic junction is provided. In a preferred form of the solar cell device disclosed herein, a single layer of graphene or no more than a few layers of graphene surrounds the zinc oxide nanowire. The outstanding performance of the solar cell device of this embodiment requires high quality and uniformity of the ultrathin graphene coating the zinc oxide nanowire. A new method for achieving this is disclosed, which involves forming a graphene shell by thermal conversion from at least one polycyclic aromatic hydrocarbon precursor. In another method, the coating technique includes surrounding the nanowire core with a solution containing graphene oxide, followed by thermal reduction of the graphene oxide to form a shell of reduced graphene oxide conformally disposed around a portion of the corresponding nanowire core.

[0070] In one aspect, the side of the graphene facing away from the zinc oxide is in contact with a material that is effective to further reduce the work function of the graphene. In this way, the difference in the work function of the materials that make up the solar cell is increased, thereby increasing the built-in potential that determines the open circuit cell voltage. Techniques for achieving this enhancement are also disclosed herein. For example, the electrode in contact with the graphene-based shell can be formed of a metal, such as silver, which reduces the work function of the graphene when in contact with the graphene. In another form, this metal is provided as a colloidal suspension in a partially transparent conductive material (such as indium tin oxide) to form an electrode that performs the dual function of transmitting current and increasing the cell potential by reducing the graphene work function. So constructed, the solar cell device according to the present invention can achieve an open circuit cell voltage that is significantly greater than that obtainable using a conventional silicon-based solar cell design.

[0071] These and other coating methods, as well as the unique and important optoelectronic properties of the cell, are described in detail below. Manufacturing techniques, contact doping of graphene, reducing cell series resistance, increasing work function differences, and other matters related to maximizing the performance parameters of the new generation solar cells disclosed herein are described in detail below. In addition, although zinc oxide may be mentioned in many places herein, it should be understood that other wide bandgap materials may be used in some form in the alternative and / or in combination with zinc oxide.

[0072] Go to more details such as Figures 1 to 4 , a schematic diagram of a nanowire core-shell radial heterojunction solar cell is shown. Figure 1 , provides an illustrative example of a solar cell device 20. The device 20 includes a plurality of nanowire cores 22 having a cladding 24 thereon. In one form, the cladding 24 extends over the top of the nanowire cores 22, as shown by reference numeral 26. Figure 1A An enlarged view of a portion of one nanowire core 22 and cladding 24 is shown.

[0073] The device 20 also includes a first electrode 30 and a second electrode 32. In one form, the first electrode 30 includes a substrate 34, which can be provided for growing the nanowire core 22. The first electrode can include any number of additional materials and layers to improve overall electron migration and / or reduce resistance. For example, the first electrode 30 can include a contact layer 36 for providing appropriate contact between the substrate 34 and other components in the first electrode 30 or elsewhere in the solar cell 20. The first electrode can also include a collector 38, such as for collecting and migrating electrons at the first electrode 30.

[0074] The second electrode 32 may similarly include one or more different materials and / or layers. The second electrode 32 is generally configured to allow light and / or photons to pass through at least a portion of the electrode 32. Figure 1 As shown, the second electrode 32 is in the form of strips or other interconnected designs to allow light and / or photons to pass therethrough. In other forms, the second electrode may include at least a portion that is transparent, semi-transparent, etc.

[0075] In one form, device 20 includes an insulating layer 40 at the ends of the nanowire cores adjacent first electrode 30. Insulating layer 40 generally prevents cladding 24 from contacting substrate 34 and / or portions of first electrode 30. If cladding 24 contacts the first electrode, it may result in a short circuit in the solar cell.

[0076] Figure 2 A side view of a solar cell device 20 is shown. As shown in this figure, light, shown by arrows 50, at least partially passes through the second electrode 32 to interact with the capping layer 24.

[0077] Figure 3 Shown with Figure 2 A similar solar cell device 52 is shown. In device 52, substrate 34 and / or first electrode 30 include a masking layer 54. Masking layer 54 can be used temporarily, such as during manufacturing, or permanently to prevent nanowire core 22 from growing on all sides of the substrate. Details of masking layer 54 and its use will be discussed in further detail below.

[0078] Figure 4 Another form of a solar cell device 60 is shown. The device 60 includes an electrode component 62 that can be used as a part of the second electrode 32 and / or used in conjunction with the second electrode 32. The electrode component 62 can include at least partially transparent and / or translucent materials. The electrode component 62 can be placed on the second electrode 32, under the second electrode 32, and / or at least partially extend beyond the second electrode 32 to contact the cover 24. For example, in Figure 1In the form of the masked second electrode 32 shown, the electrode member 62 can pass between the spaces in the second electrode 32. In addition, the electrode member 62 can extend along the length of the nanowire 22 and the capping layer 24 to provide further contact therebetween. The electrode member 62 and its use will be discussed in more detail below.

[0079] There are a variety of different materials that can be used for the solar cells described herein. Typically, the coating includes graphene and graphene-related materials. For example, the coating can typically include a single layer of graphene or a few layers of graphene. In other forms, the coating material can include reduced graphene oxide. In this regard, depending on the application method, multiple layers of reduced graphene oxide will typically form the coating.

[0080] Graphene consists of a single layer of carbon that extends infinitely in two dimensions. The chemical bonds between the carbon atoms are very similar to those in graphite. Graphene has an electronic structure that gives it unique optical and electrical properties that are not found in any other material. Importantly, graphene absorbs light better than any other material and does so independently of wavelength across the entire solar spectrum. Unsupported graphene has no band gap, and the electrons behave like massless fermions. At the so-called Dirac point, coinciding with the Fermi level, the density of quantum states is zero. Because the electrons move at a large fraction of the speed of light, graphene obeys the principles of quantum electrodynamics rather than quantum mechanics.

[0081] The nanowire core may also include a variety of different materials. For example, various wide bandgap materials may be used. Such wide bandgap materials may include, but are not limited to, zinc oxide, boron, titanium, silicon borides, carbides, nitrides, oxides, or sulfides, combinations thereof, and the like. Wide bandgap materials will be understood to refer to materials having a valence band and a conduction band that differ by at least 2 volts. In one form, zinc oxide may be particularly suitable for at least some of the techniques and material combinations discussed herein.

[0082] Zinc oxide has excellent optoelectronic properties. For example, density functional calculations show that there is a strong attraction between zinc oxide and graphene (enhanced by nanowires) due to dipole-induced dipole electrostatic interactions (accompanied by only a small amount of electron migration). This "contact" interaction profoundly changes certain electronic properties of graphene, such as the work function, while retaining the desired electronic structure and other electronic properties, such as the Dirac point of graphene. The results show that the work function of wide-bandgap ZnO (3.37 eV) is very surface sensitive and can increase by up to 2.8 eV when in contact with selected substances. Therefore, due to the contact between the two materials, the work function of graphene decreases, while the work function of zinc oxide increases, allowing graphene to be used as a photoactivated material. The change in work function is due to the charge redistribution that occurs when graphene comes into contact with zinc oxide, which interacts with zinc oxide in just the way it needs to, probably because its bipolarity allows it to act as an electron acceptor.

[0083] The solar cell devices disclosed herein were developed to test the speculation based on these theoretical considerations that the resulting large difference in work function may make the graphene / ZnO junction favorable for charge separation. The results of the experimental tests disclosed herein to test these speculations confirm that the graphene / ZnO heterojunction is indeed capable of generating large photocurrents and photovoltages and is a good candidate material for a new generation of high conversion efficiency solar cells.

[0084] As more fully described in the discussion below, Applicants have developed novel heterojunction solar cell architectures and related manufacturing methods based on pn junctions, such as in the form of zinc oxide nanowires radially coated with a single layer or at most a few layers of graphene or reduced graphene oxide. The ZnO nanowires provide high voltage and facilitate current transport, while the graphene material absorbs the entire spectrum of sunlight and generates current as electrons are accelerated into the ZnO nanowire core. The graphene material generates contact charge due to charge redistribution at the graphene-ZnO interface, resulting in an increase in the work function of ZnO and a decrease in the work function of graphene. As a result, the "effective work function" of the solar cell (the difference in the work functions of the materials that make up the pn junction forming the cell) is increased, and the solar cell is therefore operated at voltage levels much higher than those previously achieved in silicon-based or other existing solar cell architectures.

[0085] As further described and demonstrated below, the present teachings enable the production of photovoltaic solar cells that exhibit open circuit cell voltages exceeding 2.4 V and up to at least 3.5 V. Through optimizations related to improved series resistance, coating uniformity, and recombination kinetics, the disclosed architecture should provide photocurrent levels that result in conversion efficiencies far exceeding those of cells used in today's photovoltaic devices.

[0086] In one approach, the nanowire core is formed of a material that effectively distributes charge to the graphene upon contact, resulting in an increase in the work function of the material while reducing the work function of the graphene. Suitable core materials may also have an attractive potential for graphene, making them a catalyst for the thermal decomposition and simultaneous conversion of one or more aromatic precursors to form one or more layers of graphene shells encapsulating the nanowires. The shell / coating 24 comprises a graphene material, which in a preferred form comprises graphene or reduced graphene oxide, and is preferably conformally disposed around at least a majority of the core 22. As used herein, such reference to "majority" will be understood to refer to an amount disposed over approximately fifty percent or more of the surface area of ​​the nanowire. In general, a viable solar cell will include a plurality of such nanowire cores 22, each nanowire core 22 having a shell 24 of graphene material disposed therearound.

[0087] In one approach, the nanowire core comprises zinc oxide. In other forms, zinc oxide constitutes from about 50% to about 100% of the nanowire core. As used herein, "consisting essentially of a material" will be understood to refer to an amount greater than fifty percent. In one form, the nanowire core consists essentially of zinc oxide, such that at least fifty percent of the nanowire core is zinc oxide. Reference to a core 22 consisting essentially of a material will be understood to refer to a core 22 that is essentially pure in these respects, but which may include trace amounts of impurities and dopants, for example, purposefully introduced n-type or p-type dopants designed to elicit desired electrical properties.

[0088] The nanowires are typically arranged on the foil so that they extend from the foil in a generally lateral manner. In a preferred form, the nanowires may be arranged so that the longitudinal axes of at least most of the nanowires are substantially aligned with each other and extend generally perpendicular to the foil. As used in these aspects, "substantially aligned" will be understood to mean within 25 degrees, and "substantially perpendicular" will be understood to mean extending at an angle of between 70 degrees and about 110 degrees relative to the substrate. In particular, by one approach, the orientation of these longitudinal axes is also substantially coaxial and parallel to the intended beam.

[0089] The bottom of the resulting nanowire nanostructure is attached to the foil substrate 34, thereby electrically connecting all of the cores 22. The top of the nanowire carries a cladding, such as a graphene material, which is in electrical contact with all of the coaxial shells 24 surrounding the nanowire cores 22. Thus, the growth process automatically creates a solar cell nanostructure that provides separate electrical connections to the cores 22 and shells / claddings 24.

[0090] The thickness of these shells / coatings of graphene material 24 can vary with the application environment. However, in order to maximize the battery voltage, the thickness is preferably from about one layer to several layers. Therefore, for many purposes, the thickness of shell 24 is very thin. In general, when used in a photovoltaic environment, the number of layers needs to be no more than the number of layers required to achieve a specific amount of light absorption. It can be assumed herein that for a given object, shell 24 has a substantially uniform thickness, but if necessary and / or suitable for the needs of a given application environment, these teachings will adapt to changes in these aspects. For example, in some application environments, it may be useful if shell 24 has no more than about ten layers of graphene material. In a preferred form, the graphene material is substantially 1 atom thick graphene, and in other forms, the thickness along the length of the nanowire is in the range of 1-3 layers thick. When the graphene material is reduced graphene oxide (r-GO), the preferred thickness is 2-10 layers thick.

[0091] By one approach, dark current and majority carrier migration can be minimized by preventing the coaxial graphene material shells 24 from contacting the foil substrate 34. This can be accomplished, for example, by chemical vapor depositing a single or multiple layer of insulator 40 in the spaces between the nanowire cores 22 prior to depositing the graphene material shells 24. Alternatively, the insulating layer 40 can be formed during the hydrothermal growth of the nanowire cores themselves, as described further below.

[0092] according to Figure 1 The solar cell devices designed and utilizing ZnO nanowire arrays shown can take advantage of the unique optoelectronic properties of ZnO nanowires. Bulk ZnO is an insulator and, although it has considerable electron mobility, is generally considered unsuitable as a solar cell material due to its relatively high resistivity. Despite this, the electron mobility of bulk ZnO is very limited due to surface conductivity. By constructing ZnO in the form of nanowires, the surface conductivity is greatly improved, presumably because the surface to volume ratio in nanowire form is several orders of magnitude greater than in bulk form. Nanowires of this material are very good electrical conductors compared to bulk ZnO.

[0093] A single layer of graphene absorbs 2.3% of solar radiation, and this absorption is independent of wavelength in the infrared to ultraviolet region of the spectrum. The zinc oxide nanowire is preferably uniformly coated with graphene along its entire length to ensure optimal absorption of solar radiation. In order for a single layer of graphene cladding to absorb all incident solar radiation, the graphene coating area must be at least 43 times the area of ​​the wire. By coating the nanowire with graphene, the graphene area exposed to sunlight is easily increased by two orders of magnitude compared to the "wire" area of ​​the cell itself. In one aspect, the nanowire diameter and aspect ratio are selected to meet this requirement. Thus, the nanowires including the nanowire core can have a longitudinal length exceeding hundreds of nanometers. For example, the length of the nanowire can be in the range of about 5 to about 25 microns, and in a given solar cell, the length of a single nanowire can be slightly different. The length of the nanowire can be adjusted by changing the concentration of the starting material. The cross-sectional diameter of the nanowire is preferably about 40 to about 500 nanometers, although these teachings will apply to nanowires of other diameters. The nanowire core is characterized by an aspect ratio (length divided by diameter) of about 10 to about 250.

[0094] The creation of this core / shell axial heterostructure allows the absorption of the total solar flux over a significantly reduced "wire" area of ​​the solar cell material. Each of the large number of such nanowires present in the photovoltaic device contains a unique structure that acts individually as an effective nanoantenna and light rectifier. Calculations for cylindrical nanowires with a radius of 20 nanometers show that total light absorption occurs for a nanowire length of about 400 nanometers (which is in turn within the visible light wavelength range). Therefore, it can be seen that each nanowire possesses both the light-concentrating (electromagnetic wave) capabilities of an antenna and the rectifying properties of a photovoltaic device.

[0095] According to the teachings herein, the surface density of nanowires can also be optimized to manipulate the optical and electrical properties of solar cell devices. In this regard, the surface density can be characterized as the number of nanowires per unit substrate area, or as the proportion of the substrate area occupied by the nanowires. The surface density can be determined, for example, based on measurements of nanowire diameters and inter-nanowire distances obtained from SEM images of nanowire arrays.

[0096] As will be appreciated by those skilled in the art of hydrothermal growth of nanowire arrays, the surface density of the nanowires can be controlled by manipulating factors such as the chemistry of the precursor solution, the temperature at which the nanowires are grown, the concentration of the nucleating material used, the surface roughness and crystallinity of the seed layer, and other conditions. In one form, the nanowires are grown so that there is a high surface density of nanowires thereon. It is generally preferred that the nanowire array be as dense as possible to maximize the power output per unit area of ​​the solar cell device. However, if the surface density is too high, it is difficult to uniformly coat the graphene over most of the length of the nanowires. The density and spacing of the nanowires should be as high as possible, while leaving enough spacing to enable the coating of graphene and so that adjacent coated nanowires do not contact each other to prevent short circuits in the solar cell. In one form, the surface density, in terms of the percentage of the substrate area in contact with the grown nanowires before coating with graphene, is about 10% to about 80%, although it can be more if appropriate.

[0097] Those skilled in the art understand the hydrothermal synthesis process of forming ZnO nanowire arrays on many different metal foils. The foil substrate can therefore include a variety of metals, including, for example, zinc, aluminum, steel or copper, just to name a few examples. The thickness of the foil can vary depending on the application environment. For many purposes, the thickness of the foil is very thin to make the solar cell device flexible so that surfaces of various shapes can be coated. However, in general, thicker foils are stronger. For many applications, the foil is thin enough to be flexible, but thick enough to avoid tearing or breaking during use. If required for cost or other reasons and / or suitable for the needs of a given application environment, these teachings will accommodate changes in the selection of foil materials and foil thickness.

[0098] By one method, a substrate is provided as a zinc foil, and a hydrothermal synthesis process is used to form a substantially aligned array of zinc oxide nanowires for use as the nanowire core 22. The ZnO nanowires need to be in ohmic contact with the first electrode. In one method, this can be achieved by hydrothermal synthesis on a zinc metal foil using an aqueous solution of zinc acetate and hexamine. The presence of hexamine (hexamethylenetetramine) promotes highly anisotropic growth conditions because non-polar ZnO crystal planes are selectively capped. As an illustrative example of these aspects (but not intended to imply any particular limitation of these aspects), aligned ZnO nanowires can be grown using an aqueous solution of 50 mM zinc acetate and 50 mM hexamine in contact with a 100 micron thick zinc foil at 90° C. for 4 hours. Using this method, the nanowires have a diameter of 100 to 200 nm and a length of 10 to 15 microns, and a substantially continuous coating of non-conductive zinc oxide is formed on the foil substrate between the ZnO nanowire cores.

[0099] In another approach, ZnO nanowires may be grown at high temperature using water as an oxygen source, as used in the zinc plating process. In yet another form, a seed layer may be used to grow the nanowires.

[0100] Figure 6 This is a field emission scanning electron microscope image taken from one end of a ZnO nanowire array formed in this way. The nanowires have a hexagonal cross-sectional geometry and are substantially aligned along their longitudinal axis. Raman vibrational spectroscopy analysis of such ZnO nanowires based on inelastic scattering is shown in Fig. 9 The lower part is shown. The lower curve is 438.78cm -1 The E2 vibration mode peak at indicates that the ZnO is essentially pure.

[0101] If the hydrothermally grown nanowires are too long, their ends may Fig.18 The characteristic "flower" growth pattern shown in the central region of the FESEM image radiates outward. While not necessarily detrimental to cell performance, this is best avoided because it makes it more difficult to uniformly coat the nanowires with graphene.

[0102] In order for the foil to be used as an electrode, one side should be protected from nanowire growth. This can be achieved by coating the foil with a polymer film or coating (e.g. Figure 3 The protective polymer coating is then removed, typically after coating the nanowires with the graphene material, such as by dissolving using one of a variety of different organic solvents. In one form, such a technique has been developed to protect one side of the zinc foil from the growth of ZnO nanowires using polymethyl methacrylate (PMMA). Any alternative plastic coating or film that can withstand the temperature conditions of the nanowire growth and coating steps may be used.

[0103] An alternative method to prevent the nanowires from growing on both sides of the foil is to fold the foil in half so that the two sides are touching. This prevents the growth solution from reaching the protected side, thereby allowing the nanowires to grow only on the two exposed sides. After coating the nanowires with the graphene material, the folded foil is restored to a single foil form.

[0104] The power output of a solar cell is a function of the current, so it is preferred to minimize the series resistance of the cell. The series resistance in a solar cell is a combination of the resistance of the current flowing through the emitter and base of the solar cell, the contact resistance between the electrode and the photovoltaic junction material, and the electrode resistance. The sheet resistance of the nanowire array is the main contributor to the series resistance of the solar cell disclosed herein. The sheet resistance is used to characterize the resistance to current flowing along the surface of the thin layer (rather than perpendicular to the thin layer).

[0105] By one approach, the nanowires 22 can be subjected to a post-growth annealing process to reduce their surface defects and increase surface conductivity in a controlled manner. The annealing process can include heating the nanowire / foil composite in an oxygen atmosphere or by using other conventional techniques. Fig.15 The effect of annealing ZnO nanowire arrays in an oxygen atmosphere at 350 °C for up to 8 hours before being coated with graphene is shown. 2 The nanowire arrays were annealed and their sheet resistance was directly measured using a conventional four-point probe measurement setup. After annealing for 2 hours, the sheet resistance dropped significantly and by two orders of magnitude after 8 hours.

[0106] Further reductions in series resistance will result in a proportional increase in photocurrent. It is believed that this can be achieved by annealing at temperatures above 350°C. For example, although zinc has a relatively low melting point (about 420°C), such higher temperature annealing can be performed by contacting a zinc foil substrate with a copper foil to form brass by diffusion, thereby raising the melting point and allowing further reduction of surface defects on the zinc oxide nanowires under higher temperature conditions.

[0107] Post-growth annealing can also improve the diode properties of the nanowires. As will be appreciated, the pn junction formed by radially wrapping graphene around the ZnO nanowire acts as a diode that conducts current primarily in one direction. ZnO is initially an n-type semiconductor, but when in contact with the graphene material, the ZnO migrates excess electrons to the graphene, which becomes an n-type region containing negatively charged electrons, while the ZnO becomes a p-type region containing positively charged carriers. As demonstrated by experimental studies described in more detail below, the graphene cladding absorbs photons of sunlight, and electrons flow from the graphene to the ZnO.

[0108] The effect of oxygen annealing was also shown to significantly improve the cell rectification factor. In this context, the cell rectification factor is understood to refer to the ratio of the forward current to the reverse current. In a study conducted on r-GO / ZnO heterostructures before and after O2 annealing at 400°C for 8 hours, the rectification factor increased from 0.52 to 1.82 (a 3-fold increase), indicating that the forward current was much higher than the reverse saturation current. Having a good rectification factor affects the ideality of the fabricated diode for optoelectronic applications. A lower reverse saturation current is preferred to avoid leakage current and less observed voltage under solar exposure.

[0109] In another aspect, doping of the nanowire core 22, such as by adding dopants to the growth solution, can be used to increase its conductivity in a controlled manner as a technique for reducing the series resistance of the solar cell device. In one aspect, one or more dopants are included along at least a portion of its longitudinal surface. The dopants can include, but are not limited to, at least one of aluminum, indium, chlorine, and gallium. This doping method can help optimize the properties of the junction between the nanowire core and the cladding (such as a graphene-zinc oxide junction) to produce a solar cell that exhibits maximum efficiency in converting light into electricity.

[0110] After formation and any subsequent annealing and / or doping steps, the aligned zinc oxide nanowires 22 can be exposed to a coating process to deposit graphene material along the longitudinal surfaces in the spaces between the wires and on the top surface of the nanowire core 22 itself. By one approach, the coating or shell 24 can be composed primarily of reduced graphene oxide and / or graphene and include, for example, a few layers to a thickness of no more than about ten layers. For example, the Hummers method (WS Hummers and RE Offeman, JACS, 1958) can be used to synthesize a few layers of micron-sized graphene oxide flakes (GO) for use as a coating for ZnO nanowires. Graphite is treated using well-known processes, including the use of nitric acid and sulfuric acid and KClO3 or KMnO4 as oxidants to prepare graphene oxide (GO).

[0111] The coating of ZnO nanowires can be performed by drop casting an aqueous suspension of graphene oxide onto the aligned ZnO nanowire arrays and then heating to a temperature of about 300°C in a hydrogen environment for about 2 hours. Various other methods, such as drop coating, dip coating and spin coating, can also be used alternatively to surround the nanowires with graphene oxide. By heating in a hydrogen atmosphere, the graphene oxide flakes are thermally reduced. Some oxygen remains in the substitutional position, resulting in reduced graphene oxide, a disordered form of a few layers of graphene. Prior to drop casting, the uniformity of the coating is improved by adding isopropanol or acetone to the aqueous suspension as a wetting agent. In order to prevent short circuits, it is desirable that the reduced graphene oxide does not contact the Zn foil or substrate carrying the ZnO nanowires.

[0112] Other methods of surrounding the ZnO nanowires with a thin layer of r-GO are also possible. For example, known methods of dissolving r-GO flakes to form a solution or preparing a colloidal suspension of r-GO flakes can be used so that the nanowire coating process can be carried out from solution. In this method, a solution or a stable colloidal suspension of r-GO flakes is applied to the nanowires and optionally heated to evaporate the solvent to remove impurities. Alternatively, this method can be used to coat the nanowires with graphene from a solution of graphene nanosheets.

[0113] Figure 7 Figure 1 is a field emission scanning electron microscopy examination of ZnO nanowires coated with r-GO after hydrothermal growth and oxygen annealing. FESEM morphology characterization shows an approximate length of about 10 microns, vertically aligned with some horizontal wires on top of parallel vertically ordered ZnO nanowires. It can be clearly observed that the r-GO coating is a transparent thin layer wrapped around the ZnO nanowires and covers the top surface, and forms a good interfacial contact with the semiconductor. Compared with the hexagonal uncoated nanowires, the coated nanowires are more rounded, indicating that the r-GO coating is several layers thick.

[0114] Raman vibrational spectroscopy analysis was also performed to illustrate the presence of the ZnO core and r-GO shell in the coaxial heterostructure. One such spectrum is Fig. 9 The ZnO sample shows the corresponding ZnO peak E2 due to the in-plane vibration of the Zn-O bond. low (low, low) and E2 high (high). The r-GO / ZnO heterostructure exhibits an E peak based on in-plane vibration as well as an A peak attributed to the out-of-plane vibration of the Zn-O bonds. In addition, the defect-induced “D” and graphitic “G” modes observed in the r-GO / ZnO nanocomposites indicate the presence of r-GO.

[0115] With Figure 1 An r-GO-coated ZnO nanowire heterojunction photovoltaic cell with a patterned silver electrode as generally shown in FIG. 1 and in contact with r-GO according to the disclosed principles has achieved an open circuit voltage of up to about 2.4 V, which is significantly higher than any previous single junction solar cell known to the applicant. In comparison, the open circuit cell voltage of silicon-based solar cells typically does not exceed 0.6 V. Fig.11 The following figure shows the use of 1KW / m 2Current density-voltage curves for five such cells irradiated with AM 1.5G irradiation. As will be appreciated, AM 1.5G is a standardized spectrum close to the overall annual average solar irradiance in the mid-latitudes of the United States, and is used by the solar industry for standardized testing or rating of terrestrial solar cells or modules. (The latest AM 1.5G standards related to photovoltaic applications are reflected in ASTM G-173 and IEC 60904.) Current and voltage curves were generated using a standard Keithley source meter. The differences observed between the current density and voltage curves of individual cells may be attributed to factors such as variations in r-GO coating uniformity and / or nanowire size and density.

[0116] Based on the very large work function increase of 2.8eV that occurs when ZnO is in close contact with a strong electron acceptor, the observed large open circuit voltage (i.e., the voltage when the total current through the solar cell is zero) can have a reasonable explanation. Graphene can play this role in the case of ZnO as an electron donor due to its amphoteric properties. Due to the interfacial charge transfer between r-GO and ZnO, ZnO provides electrons to graphene. Therefore, the work function of ZnO increases by about 1eV, while the work function of r-GO decreases. When irradiated, photons generate excitons (bound electron-hole pairs) in the outer r-GO shell, and due to the presence of a built-in potential, the excitons dissociate at the heterojunction. Electrons migrate from low work function graphene to high work function ZnO.

[0117] The research on which this disclosure is based also demonstrates that graphene acts as a photoactive element by following the photocurrent as a function of wavelength. Fig.16 As shown, the normalized photocurrent generated from the heterostructure (i.e., the current corrected for the sensitivity of the phototube measuring device) is essentially constant over a wide wavelength range of 200 to 1100 nm. This indicates that the generation of excitons occurs in r-GO because ZnO does not absorb light in the visible region of the spectrum. r-GO can absorb all sunlight energy corresponding to UV-Vis-lR wavelengths from 200 to 1100 nm and up to IR. The maximum absorption of r-GO occurs at 290 nm, which is located in the UV region; however, most of the sunlight energy is actually in the visible region and can only be absorbed by r-GO in the ZnO / r-GO heterostructure.

[0118] Since the normalized current data show a stable photogenerated normalized current of 0.6-0.7 from 200 to 1100 nm, it can be concluded that the uniform r-GO-coated ZnO nanowires absorb solar energy from the entire solar spectrum, generating a photocurrent that is independent of the observed wavelength. No significant photocurrent was generated using ZnO nanowires without graphene coating because ZnO is a wide-bandgap semiconductor (3.37 eV) and sunlight in the UV part of the spectrum is required to photoexcite ZnO orbital electrons from the valence band to the conduction band, thereby generating electron-hole pairs. Since essentially all of the solar spectrum is below UV energy, the electron excitation to form electron / hole pairs occurs essentially only in graphene. Charge separation occurs at the junction of graphene and ZnO, generating photocurrent at cell voltages up to 2.4 V.

[0119] Fig.17 The experimental results shown show that the magnitude of the photocurrent depends linearly on the light intensity over a range of three orders of magnitude. When using an AM 1.5G light source, the photocurrent is 4.14 μA, while when using monochromatic light, the photocurrent is 3.46 nA. The AM1.5G light source includes all wavelengths of the solar spectrum. Its intensity is measured to be three orders of magnitude higher than the light intensity of the monochromatic light source.

[0120] Yet another aspect of the invention relates to enhancing the open circuit cell potential by contacting at least a portion of the outer surface (i.e., the surface facing away from the ZnO core) of a coating or shell (e.g., r-GO shell) with a material that acts as an electron donor to the graphene. In a preferred aspect, the electron donor material may also serve as a current collecting electrode. For example, such an electrode may be formed by depositing a silver nanoparticle paste through a patterned mask placed on the cell r-GO termination surface. Figure 1 In the embodiment shown, the metal is patterned into a series of spaced apart elongated fingers extending perpendicularly from the busbar, which allows for sufficient surface contact between the metal and the r-GO shell. 1 cm 2 The prototype of the battery Figure 5 , which shows the top of the cell, with the silver layer contacting the top surface of the r-GO coated ZnO nanowire array. Sunlight penetrates between the narrow silver fingers to illuminate the graphene. The metal layer can be provided in other geometries that can function similarly to form surface contact with the r-GO shell while allowing sufficient sunlight to penetrate. In this way, the significant photon absorption properties of the nanowire array coated with rGO are exploited, and the array constitutes an important component of the solar cell device.

[0121] Silver acts both as an n-type contact dopant and as an electrode. The silver electrode effectively increases the open circuit potential to about 2.4 V. While not wishing to be bound by any theory, this effect may be the result of a similar charge redistribution between the metal and r-GO, resulting in contact charging that reduces the work function of the r-GO shell by an amount corresponding to the observed increase in the cell open circuit potential. As described below, this effect has also been demonstrated in an alternative embodiment having a shell of essentially a single layer of pure phase graphene produced from a polyaromatic precursor. In fact, by judicious contacting of a single layer graphene / ZnO nanowire / silver composite, an increase in the open circuit voltage to 3.5 V was found. In addition, it is believed that similar improvements may be achieved by using other nanowire core materials and by using other electron donor contact charging materials that can also serve as electrodes.

[0122] Therefore, by one approach, both sides of the graphene-based shell are used to reduce the work function of graphene, thereby increasing the open circuit battery potential. In such an embodiment, the graphene coating or cladding is essentially charged by two "plates" to develop a huge built-in potential. Although the significant performance advantages of this important discovery have been demonstrated using silver, other metals such as aluminum and copper reduce the work function of graphene by providing electrons to graphene. In addition, in the dual contact charging configuration disclosed herein, materials such as ZnO can also be used as contact charging materials. The teachings of this article will enable a person skilled in the art to identify other suitable alternative contact charging materials by comparing the cell voltage measurements of solar cells manufactured with and without contacting the candidate material with the graphene material shell.

[0123] The arrangement for achieving double contact charging is not limited to contacting the electron donor with the end of the nanowire, such as Figure 1 As shown. For example, the electron donor may alternatively be arranged to contact a location along the length of the nanowire. Combinations of these approaches may also be effective. According to another aspect described in more detail below, the selected charging material is incorporated into another material, such as an organic or inorganic transparent electrode conductive material, which serves as an electrode on the graphene side of the photovoltaic junction.

[0124] Returning to the methods for coating ZnO nanowire cores according to the disclosure herein, in another approach, the nanowires are coated with an ultrathin coating consisting of a single layer to no more than a few layers of graphene. Polycyclic aromatic hydrocarbons (PAHs) such as hexanes, pentacene, naphthalene, etc., thermally decompose on metals such as copper to form single layers of graphene at appropriate temperatures. However, it was previously unknown whether similar results could be obtained with ZnO nanowires. Additional research led to the discovery of techniques utilizing these precursors that are effective in depositing one to a few layers of substantially pure phase graphene substantially uniformly along a majority of the outer surface of the ZnO nanowire.

[0125] As an example of this newly developed coating technique, hexadecene was dissolved in tetrahydrofuran and then drop-cast onto a ZnO nanowire array grown hydrothermally on Zn foil. The assemblies were heated in an argon atmosphere at 200°C to 400°C for 1 to 2 hours. The thin layer of solution in contact with the ZnO decomposed to form graphene, and the rest evaporated.

[0126] refer to Fig.10 , Raman spectroscopy examination showed that the thermal decomposition indeed led to the formation of high-quality graphene, as evidenced by a G / D band intensity ratio of about 2.0. Electron microscopy images of the coated nanowires, such as Figure 8 The image shown in , shows that the hexagonal faces of the nanowires are preserved, which means that the growth of a single layer of graphene has occurred. The discovery of the solution disclosed in this article overcomes the difficult challenge of coating billions or even trillions of densely packed nanowires with graphene, which is of great significance for the commercial scale production of high-efficiency solar cell devices. It is believed that theoretical density functional calculations show that there is a very strong attractive potential of about 1V between graphene and ZnO, which reduces the activation energy for the conversion of PAH to graphene and in a sense becomes the driving force for the reaction. The ZnO surface can be regarded as a catalytic surface for the reaction, capable of forming an ultra-thin graphene layer on the nanowire structure at temperatures as low as 200°C. The reaction is a self-constrained reaction because once the graphene layer is formed on the surface, it will remain there, rather than leaving the ZnO surface to allow catalysis of the next PAH molecule. Although the above description uses ZnO, it is believed that other wide bandgap nanowire core materials may also be suitable for use in this manner.

[0127] Based on the insights gained from this work, other aromatic molecules, such as substituted benzenes, are also considered as suitable precursors for coating ZnO nanowires with ultrathin layers ranging from one to a few layers of graphene according to the teachings of this article. This technique is also applicable to nanowires formed from other materials that exhibit an attractive potential towards graphene, as determined by theoretical density functional calculations.

[0128] The present invention discloses a technique for coating high-density nanowire arrays with ultra-thin graphene coatings, which is of great significance for the production of high-efficiency solar cells. 2Under AM 1.5G irradiation, an open circuit voltage of about 1.9V was observed for this graphene-coated ZnO nanowire solar cell, even in the absence of contact charging of the graphene with a metal electrode to reduce its work function. In combination with a silver electrode in contact with the graphene shell, an open circuit cell potential of up to 3.5V was observed. Compared with the r-GO-coated solar cell device, it is believed that this type of solar cell device achieves a higher cell potential, which is due to the higher graphene quality of the single or few-layer graphene produced from polycyclic aromatic hydrocarbons. Since contact charging is an electrostatic phenomenon, the charge transferred from the metal layer is distributed on the single-layer graphene, rather than on the few-layer graphene. Therefore, it can be expected that the transferred charge will lead to a higher graphene charge density. In this way, the built-in potential increases, resulting in the observed increase in the open circuit potential.

[0129] The ultrathin graphene coating obtained by thermal conversion of PAHs reduced the width of the junction to about 2 to 3 angstroms, while the width of the ZnO nanowires coated with multilayer r-GO was about 8 to 9 angstroms. In addition to the higher graphene quality, this may be another reason why single-layer graphene performs so well in this photovoltaic device.

[0130] In yet another aspect, the graphene shell can be doped to further control the work function of the graphene. In particular, by heating in, for example, an ammonia atmosphere, doping the shell with an n-type dopant such as nitrogen or other n-type dopant, the work function of the graphene can be further reduced by at least 0.5 V, which can further enhance the open circuit potential. It should also be kept in mind that the open circuit voltage is unlikely to exceed the band gap of the material constituting the nanowire core.

[0131] The open circuit voltage of graphene-based nanocomposite photovoltaic devices is as high as 3.5 volts, which enables a new class of potentially high-efficiency solar cells. In addition to high open circuit voltage, high short circuit current is also necessary to achieve high power conversion efficiency. As mentioned above, since the current flows on the surface of the ZnO nanowires, the current density can be increased by controlling the nanowire growth conditions to increase the surface-to-volume ratio of the nanowires by reducing the diameter of the nanowires.

[0132] It is believed that another factor affecting the short-circuit current of devices made according to the disclosure herein involves electron / hole recombination kinetics. It is reported that in pristine graphene, the exciton lifetime does not exceed a few femtoseconds. The recombination kinetics can compete strongly with the migration of electrons across the heterojunction. To address this issue, a suitable dopant can be found to increase the exciton lifetime, thereby increasing the photocurrent. The inclusion of one or more such dopants in the graphene or r-GO shell can lead to more favorable electron / hole recombination kinetics and increase the photocurrent generated by the disclosed solar cell device.

[0133] On the other hand, the photocurrent performance of solar cell devices can be optimized by including conductive materials to establish electrical contacts between nanowires. Transparent conductive oxides, such as indium tin oxide (ITO), or conductive transparent oxides or sulfides based on ZnO, for example, can be effectively used for this purpose and can be arranged between nanowires. Indium tin oxide is selected because it is easily available. It is deposited as a thin film by drop coating. Alternatively, indium tin oxide films can be deposited by many other techniques, such as spray or spin coating, physical vapor deposition, electron beam evaporation or a range of sputtering deposition techniques. Other suitable optically transparent conductors include conductive organic polymers, such as polyethylene dioxythiophene polystyrene sulfonate (PEDOT:PSS) and many other polymers, which can be deposited in organic solvents or aqueous suspensions.

[0134] Conductive materials can be located on top of the cell to form all or part of the counter electrode, and / or in the interstitial spaces between graphene or r-GO coated nanowires in the array. In another study, a significant reduction in series resistance was achieved by drop casting a nano-indium oxide / tin oxide isopropanol suspension on the top graphene end face of the nanowire array. In this way, electrical contact was established between the graphene-coated ZnO nanowires. The resulting impact on cell performance is discussed in conjunction with the experimental results described further below.

[0135] On the other hand, the transparent conductive electrode material can include a metal that effectively reduces the work function of graphene, thereby enhancing the voltage and current density performance of the cell. For example, a colloidal suspension of silver nanoparticles in ITO is applied to a graphene nanowire array to form an electrode and improve charge mobility within the array. Alternatively, silver or another metal can be applied to a nanowire array coated with graphene, followed by drop casting of an ITO suspension to fill the spaces between the nanowires and form the top conductive layer of the solar cell.

[0136] Additional experimental results demonstrating the effectiveness of the principles disclosed herein in optimizing the photovoltaic properties of the radial heterojunction solar cells disclosed herein will now be discussed. Fig.12 The current density-voltage curves for a cell with a core-shell heterojunction of graphene-wrapped ZnO wires grown on zinc foil and coated by hydrothermal decomposition of hexaphenylene are shown. In this particular cell, the copper electrode is in electrical contact with the zinc substrate. ITO is deposited between the nanowires and on top of the cell to increase the electrical contact between the nanowires and to provide a counter electrode for the graphene coating. Each line represents the current density at 1 KW / m 2 Measurements obtained by contacting different points of the battery under AM 1.5G irradiation. The data show that the open circuit voltage of the battery is as high as about 1.9V, and the short circuit current density is at a low mA / cm 2These results indicate that the surface interaction between ZnO and an ultrathin, essentially phase-pure graphene overlayer can generate a large cell potential even without contacting the reverse side of the doped graphene.

[0137] Fig.14 The method corresponding to the embodiment of FIG. 1 is shown except that a silver electrode is applied to the nanowire array and ITO is deposited on the silver electrode. Fig.12 The open circuit cell voltage increases significantly to about 3.5 V, which is due at least in part to the effect of silver in reducing the work function of the graphene shell, thereby increasing the difference in work function between the graphene and ZnO components of the heterojunction.

[0138] The effectiveness of ITO in increasing the photocurrent was further investigated by constructing a cell with a graphene-wrapped ZnO wire array supported on zinc foil and a patterned silver electrode instead of the ITO electrode of the previous example. The current density-voltage curve of this cell is shown in Fig.13 Although the battery exhibits an open circuit cell voltage of about 3.2 V, its short circuit current density is significantly lower than that of the battery with a voltage corresponding to Fig.14 The short-circuit current density achieved in the ITO battery. Fig.14 The significantly higher current density shown is at least partially due to the effect of the ITO.

[0139] While solar cells using ZnO nanowire cores demonstrate the principles disclosed herein, these teachings can be extended to other wide bandgap nanowire materials, such as borides, carbides, nitrides, oxides or sulfides of boron, titanium, silicon. Wide bandgap materials will be understood to refer to materials having valence bands and conduction bands that differ by at least 2 volts. The materials best suited to produce the highest solar cell potentials are those that act to contact charge graphene and exhibit a large attractive potential to graphene, thereby catalyzing the formation of a monolayer graphene shell according to the disclosed aromatic hydrocarbon decomposition method. By using an electron donor material as disclosed herein to perform additional contact charging on the opposite surface of the graphene shell, and using a transparent conductive material as an electrode material for the graphene side of the photovoltaic junction, various high voltage solar cells can be provided that can have significantly higher conversion efficiencies than previously known designs.

[0140] In summary, an energetically favorable, surface-based, and radial heterojunction solar cell composed of a graphene 2D layer and a ZnO 1D nanowire is disclosed. Experiments have shown that this novel solar cell architecture is capable of producing an open circuit photovoltage of 2.4V to 3.5V under AM 1.5G illumination. Although the reported experimental results show short circuit currents in the low milliampere range, the broader teachings of this article will enable the production of solar cells with short circuit currents of at least 10mA and possibly up to 25mA. The production of a solar cell structure showing an open circuit voltage of up to 3.5V makes it possible to achieve at least 50% solar cell energy conversion efficiency by additional optimizations that increase the photocurrent to the range just mentioned. As determined by non-equilibrium thermodynamics, the upper limit of the conversion efficiency remains at 85%. This is far superior to the maximum conversion efficiency of commercial multicrystalline silicon solar cells of about 20%. In addition, the disclosed manufacturing method can be easily deployed in full-scale commercial production at a fraction of the cost of high-efficiency multi-junction cells based on exotic materials such as gallium arsenide or indium selenide, which are currently available in very small quantities at very high price points.

[0141] Techniques for increasing the photocurrent of solar cells are known in the art, and other principles for generating higher currents within the included solar cell devices have been disclosed herein. Fig.13 and Fig.14 As shown, the use of the transparent conductor ITO increases the photocurrent generated by three orders of magnitude. Choosing the best transparent conductive material, or adding colloidal metal particles to increase the conductivity of ITO, can produce even higher photocurrents. Optimizing the distribution of the transparent conductive material throughout the nanowire array can also improve the results. Annealing the nanowires to reduce surface defects has also been shown to reduce cell resistance. Improvements in annealing processes, such as the high-temperature annealing technique described in this article, are also expected to further reduce resistance and produce higher photocurrents. In addition, the current density can be increased by controlling the diameter and surface density of the nanowires to optimize the effective electron conduction surface area of ​​ZnO. One or more of these techniques, or other commonly known methods for enhancing cell conductivity, will be able to produce high-voltage solar cells with relatively high conversion efficiencies, achieving significantly shorter energy recovery times than conventional solar systems.

[0142] The discovery of cost-effective, high conversion efficiency solar cells disclosed herein has enormous beneficial consequences for humanity in the distant future. The sun provides enough energy in one hour to meet the energy needs of the global population for a year. Cheap solar energy will hasten the day when the sun fulfills its destiny to become a global energy source.

[0143] In some forms, it is desirable to design a PV cell that is suitable for large-scale economical manufacturing using non-resource-limited, environmentally benign materials. In some forms, this can be achieved by employing hydrothermal growth of ZnO nanowires coated with graphene, a pure carbon material. Going from laboratory-scale prototypes to large-scale development to meet multi-megawatt electricity needs worldwide is a challenging engineering task that is not without precedent. In some forms, the features described herein may be suitable for achieving these goals.

[0144] The new PV cells described in this paper can be flexible and easily conform to surfaces of very complex shapes. It is believed that very cost-effective modification of existing photovoltaic power plants to produce 1 terawatt of solar power will soon be achievable. By leveraging the trillions of dollars invested in PV facilities (both as central power plants and as distributed power modules on rooftops), 3 to 4 terawatts of solar power could be generated at a very low cost, instead of 1 terawatt.

[0145] The flexibility granted by using metal foil substrates opens the door to new markets for PV power generation. For example, the roof of a car could be an obvious application. Other uses and implementations could also be exploited.

[0146] Those skilled in the art will appreciate that various modifications, changes and combinations may be made to the above-described embodiments without departing from the scope of the present invention, and these modifications, changes and combinations will be deemed to be within the scope of the inventive concept.

Claims

1. A photovoltaic solar cell device comprising at least one solar cell, wherein the at least one solar cell is prepared by a method comprising the following steps: providing a foil substrate; A plurality of nanowire cores are formed on the foil substrate using a hydrothermal synthesis process, wherein the nanowire cores comprise zinc oxide, At least a majority of the nanowire cores are substantially aligned with each other and extend generally perpendicular to the foil substrate and are electrically connected to the foil substrate at first ends of the nanowire cores, the hydrothermal synthesis process forming a substantially continuous coating of non-conductive material on the foil substrate between the zinc oxide nanowire cores; surrounding the plurality of nanowire cores with at least one polycyclic aromatic hydrocarbon; forming a plurality of nanowire core / shell structures by maintaining the nanowire core and polycyclic aromatic hydrocarbon under conditions sufficient to thermally convert at least some of the polycyclic aromatic hydrocarbon to form a plurality of shells, each shell comprising graphene and conformally disposed about a portion of a respective nanowire core to form a photovoltaic junction; forming a first conductive electrode electrically connected to the foil substrate and providing a first electrical path to facilitate movement of electrons away from the nanowire core; as well as A second conductive electrode connected to the graphene shell is formed at a second end of the nanowire core / shell structure and provides a second electrical path to facilitate movement of positive charge away from the graphene shell, wherein the second conductive electrode includes at least one metal that effectively reduces the work function of graphene.

2. The photovoltaic solar cell device according to claim 1, wherein: The substantially continuous coating of non-conductive material comprises zinc oxide.

3. The photovoltaic solar cell device according to claim 1 or 2, wherein: The at least one polycyclic aromatic hydrocarbon includes at least one of hexaphenylene, naphthalene, and terphenyl.

4. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The step of surrounding the plurality of nanowire cores with at least one polycyclic aromatic hydrocarbon comprises at least one of the following methods: spraying, drop coating, dip coating or spin coating a solution comprising the at least one polycyclic aromatic hydrocarbon in a solvent.

5. The photovoltaic solar cell device according to claim 4, wherein: The solvent includes at least one of tetrahydrofuran and dimethyl sulfoxide.

6. The photovoltaic solar cell device according to claim 4, wherein: The step of forming a plurality of nanowire core / shell structures is performed at a temperature and for a time sufficient to remove substantially all of the solvent and thermally decompose the polycyclic aromatic hydrocarbons to form graphene.

7. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The step of surrounding the plurality of nanowire cores with at least one polycyclic aromatic hydrocarbon comprises chemical vapor deposition.

8. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: Each graphene shell of the plurality of shells is conformally disposed around a majority of a corresponding nanowire core.

9. The photovoltaic solar cell device according to any one of claims 1 to 2, characterized in that: When using 1KW / m 2 When irradiated with AM 1.5G irradiation, the photovoltaic solar cell has an open circuit voltage between 1.5V and 3.6V.

10. The photovoltaic solar cell device according to claim 9, characterized in that: When using 1KW / m 2 When irradiated with AM 1.5G radiation, the photovoltaic solar cell has a power of at least 1 mA / cm 2 short-circuit current density.

11. The photovoltaic solar cell device according to any one of claims 1 to 2, characterized in that: When using 1KW / m 2 When irradiated with AM 1.5G illumination, the photovoltaic solar cell has an open circuit voltage between 2.5V and 3.6V.

12. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The foil substrate includes at least one of zinc, titanium, brass, steel, or copper.

13. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The foil substrate consists essentially of zinc.

14. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: Before the step of surrounding the plurality of zinc oxide nanowire cores with at least one polycyclic aromatic hydrocarbon, the plurality of nanowire cores are subjected to a post-growth annealing process to reduce structural defects at the surface of the nanowire cores.

15. The photovoltaic solar cell device according to claim 14, wherein: The post-growth annealing process includes heating the zinc oxide nanowires to a temperature between 350° C. and 450° C. for at least 4 hours in an atmosphere of at least 10% oxygen.

16. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The first conductive electrode is not electrically connected to the graphene shell at the first end of the nanowire core, and the second conductive electrode is not electrically connected to the nanowire core via the graphene.

17. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The shell comprises, at least over a majority, a substantially uniform single layer of graphene.

18. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The shell comprises, at least in large part, no more than three layers of graphene.

19. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The plurality of nanowire core / shell structures are arranged such that their longitudinal axes are oriented at least substantially parallel to one another.

20. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The length of the nanowire core / shell structures in the plurality of nanowire core / shell structures is in a range of 5 microns to 25 microns.

21. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: A diameter of a nanowire core in the plurality of nanowire cores does not exceed 500 nanometers.

22. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The plurality of nanowire core / shell structures are characterized by an aspect ratio of 10 to 250.

23. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The plurality of nanowire core / shell structures are characterized by a spatial density of 10% to 80%.

24. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The nanowire core includes a dopant along at least a portion of its longitudinal surface.

25. The photovoltaic solar cell device according to claim 24, wherein: The dopant includes at least one of aluminum, indium, chlorine, and gallium.

26. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The graphene shell includes an n-type dopant.

27. The photovoltaic solar cell device according to claim 26, wherein: The n-type dopant includes nitrogen.

28. The photovoltaic solar cell device of claim 26, wherein: The n-type dopant is included in the shell in an amount effective to reduce a work function of the graphene by at least 0.5 V.

29. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: The second conductive electrode is at least partially transparent to sunlight.

30. The photovoltaic solar cell device of claim 29, wherein: The second conductive electrode is a conductive inorganic material.

31. The photovoltaic solar cell device of claim 29, wherein: The second conductive electrode is a conductive organic material.

32. The photovoltaic solar cell device according to any one of claims 1 to 2, wherein: A substance effective to reduce the work function of the graphene is placed in contact with the graphene shell.

33. The photovoltaic solar cell device of claim 1, wherein: The at least one metal effective to reduce the work function of graphene includes one or more of silver, aluminum and copper.

34. The photovoltaic solar cell device of claim 1, wherein: The second conductive electrode is at least partially transparent to sunlight and includes particles of at least one metal effective to reduce a work function of the graphene.

35. The photovoltaic solar cell device of claim 34, wherein: The material forming the second conductive electrode is interspersed between the nanowire cores.

36. The photovoltaic solar cell device of claim 35, wherein: The second conductive electrode includes indium tin oxide containing silver particles.

37. The photovoltaic solar cell device of claim 35, wherein: The second conductive electrode is formed by drop coating, spray coating or spin coating.

38. A photovoltaic solar cell device comprising: a foil substrate consisting essentially of zinc; a plurality of nanowire cores on the foil substrate, the nanowire cores comprising zinc oxide, wherein at least a majority of the nanowire cores are substantially aligned with each other and extend generally perpendicular to the foil substrate and are electrically connected to the foil substrate at first ends of the nanowire cores; a substantially continuous coating of zinc oxide on the foil substrate between the nanowire cores; a plurality of shells, each shell comprising graphene and each shell being conformally disposed around a portion of a corresponding nanowire core to form a plurality of nanowire core / shell structures; a first conductive electrode electrically connected to the foil substrate and providing a first electrical path to facilitate movement of electrons away from the nanowire core; a second conductive electrode connected to the shell at a second end of the nanowire core / shell structure and providing a second electrical path to facilitate movement of positive charge away from the shell; and The second conductive electrode includes a conductive material that is at least partially transparent to sunlight and at least one metal within at least a portion of the partially transparent conductive material, the at least one metal being effective to reduce a work function of the shell.

39. The photovoltaic solar cell device of claim 38, wherein: The shell is formed of at least one polycyclic aromatic hydrocarbon including at least one of hexaphenylene, naphthalene, and terphenyl.

40. The photovoltaic solar cell device according to claim 38 or 39, wherein: Each graphene shell of the plurality of shells is conformally disposed around a majority of a corresponding nanowire core.

41. The photovoltaic solar cell device according to any one of claims 38 to 39, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G irradiation, the photovoltaic solar cell has an open circuit voltage between 1.5V and 3.6V.

42. The photovoltaic solar cell device according to claim 41, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G radiation, the photovoltaic solar cell has a power of at least 1 mA / cm 2 short-circuit current density.

43. The photovoltaic solar cell device according to any one of claims 38 to 39, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G illumination, the photovoltaic solar cell has an open circuit voltage between 2.5V and 3.6V.

44. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The first conductive electrode is not electrically connected to the graphene shell at the first end of the nanowire core, and the second conductive electrode is not electrically connected to the nanowire core via the graphene.

45. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The shell comprises, at least over a majority, a substantially uniform single layer of graphene.

46. ​​The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The length of the nanowire core / shell structures in the plurality of nanowire core / shell structures is in a range of 5 microns to 25 microns.

47. A photovoltaic solar cell device according to any one of claims 38 to 39, wherein: A diameter of a nanowire core in the plurality of nanowire cores does not exceed 500 nanometers.

48. A photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The plurality of nanowire core / shell structures are characterized by an aspect ratio of 10 to 250.

49. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The plurality of nanowire core / shell structures are characterized by a spatial density of 10% to 80%.

50. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The nanowire core includes a dopant along at least a portion of its longitudinal surface.

51. The photovoltaic solar cell device of claim 50, wherein: The dopant includes at least one of aluminum, indium, chlorine, and gallium.

52. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The graphene shell includes an n-type dopant.

53. The photovoltaic solar cell device of claim 52, wherein: The n-type dopant includes nitrogen.

54. The photovoltaic solar cell device of claim 52, wherein: The n-type dopant is included in the shell in an amount effective to reduce a work function of the graphene by at least 0.5 V.

55. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The second conductive electrode is at least partially transparent to sunlight.

56. The photovoltaic solar cell device of claim 55, wherein: The second conductive electrode is a conductive inorganic material.

57. The photovoltaic solar cell device of claim 55, wherein: The second conductive electrode is a conductive organic material.

58. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The at least one metal effective to reduce the work function of graphene includes one or more of silver, aluminum and copper.

59. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The material forming the second conductive electrode is interspersed between the nanowire cores.

60. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The second conductive electrode includes indium tin oxide containing silver particles.

61. The photovoltaic solar cell device according to any one of claims 38 to 39, wherein: The second conductive electrode is formed by drop coating, spray coating or spin coating.

62. A photovoltaic solar cell device comprising: Foil substrate; a plurality of nanowire cores on the foil substrate, the nanowire cores comprising wide bandgap material, wherein at least a majority of the nanowire cores are substantially aligned with each other and extend generally perpendicular to the foil substrate and are electrically connected to the foil substrate at first ends of the nanowire cores; a substantially continuous coating of non-conductive material on the foil substrate between the nanowire cores; a plurality of reduced graphene oxide shells, each shell being conformally disposed around a portion of a corresponding nanowire core to form a plurality of nanowire core / shell structures; a first conductive electrode electrically connected to the foil substrate and providing a first electrical path to facilitate movement of electrons away from the nanowire core; a second conductive electrode connected to the shell at a second end of the nanowire core / shell structure and providing a second electrical path to facilitate movement of positive charge away from the shell, the second conductive electrode comprising at least one conductive material effective to reduce the work function of the graphene material shell when in contact with the shell, Wherein, the second conductive electrode contacts a portion of the surface area of ​​the solar cell at the second end of the core / shell structure while exposing another portion of the surface area to sunlight.

63. The photovoltaic solar cell device of claim 62, wherein: The at least one material effective to reduce the work function of the shell includes one or more of silver, aluminum and copper.

64. The photovoltaic solar cell device of claim 62, wherein: The second conductive electrodes are in the form of spaced apart elongated strips.

65. A photovoltaic solar cell device according to any one of claims 62 to 64, wherein: The second conductive electrode also includes a material that is at least partially transparent to sunlight, and at least one metal effective to reduce the work function of the shell is located within at least a portion of the partially transparent material.

66. The photovoltaic solar cell device of claim 65, wherein: The at least one metal effective to reduce the work function of graphene is in the form of particles dispersed within the partially transparent material.

67. The photovoltaic solar cell device of claim 65, wherein: The partially transparent material of the second conductive electrode is interspersed between the nanowire cores.

68. The photovoltaic solar cell device of claim 65, wherein: The second conductive electrode includes indium tin oxide containing silver particles.

69. A photovoltaic solar cell device according to any one of claims 62 to 64, wherein: The second conductive electrode is effective to lower a work function of the shell by at least 0.5V.

70. The photovoltaic solar cell device according to any one of claims 62 to 64, wherein: The wide bandgap material of the nanowire core includes at least one of boron, iron, titanium, zinc and carbon.

71. The photovoltaic solar cell device of claim 69, wherein: The wide bandgap material also includes at least one of a boride, a carbide, a nitride, an oxide, and a sulfide.

72. The photovoltaic solar cell device according to any one of claims 62 to 64, wherein: The wide bandgap material of the nanowire core includes at least one of a boride, a carbide, a nitride, an oxide, and a sulfide.

73. The photovoltaic solar cell device according to any one of claims 62 to 64, wherein: The wide bandgap material of the nanowire core includes at least one of zinc oxide and titanium oxide.

74. The photovoltaic solar cell device according to any one of claims 62 to 64, wherein: Each shell of the plurality of shells is conformally disposed about a majority of a corresponding core of wide bandgap material.

75. The photovoltaic solar cell device according to any one of claims 62 to 64, wherein: The foil substrate includes at least one of zinc, titanium, brass, steel, or copper.

76. The photovoltaic solar cell device of any one of claims 62 to 64, wherein: The first conductive electrode is not electrically connected to the shell at a first end of the core, and the second conductive electrode is not electrically connected to the nanowire core via the shell.

77. The photovoltaic solar cell device of any one of claims 62 to 64, wherein: The shell comprises, at least over a majority, a substantially uniform single layer of graphene.

78. The photovoltaic solar cell device of any one of claims 62 to 64, wherein: The shell comprises, at least in large part, no more than three layers of graphene.

79. The photovoltaic solar cell device according to any one of claims 62 to 64, wherein: The plurality of nanowire core / shell structures are arranged such that their longitudinal axes are oriented at least substantially parallel to one another.

80. The photovoltaic solar cell device of any one of claims 62 to 64, wherein: The length of the nanowire core / shell structures in the plurality of nanowire core / shell structures is in a range of 5 microns to 25 microns.

81. A photovoltaic solar cell device according to any one of claims 62 to 64, wherein: A diameter of a nanowire core in the plurality of nanowire cores does not exceed 500 nanometers.

82. The photovoltaic solar cell device of any one of claims 62 to 64, wherein: The plurality of nanowire core / shell structures are characterized by an aspect ratio of 10 to 250.

83. The photovoltaic solar cell device of any one of claims 62 to 64, wherein: The plurality of nanowire core / shell structures are characterized by a spatial density of 10% to 80%.

84. The photovoltaic solar cell device of any one of claims 62 to 64, wherein: The nanowire core includes a dopant along at least a portion of its longitudinal surface.

85. The photovoltaic solar cell device of claim 84, wherein: The dopant includes at least one of aluminum, indium, chlorine, and gallium.

86. The photovoltaic solar cell device of any one of claims 62 to 64, wherein: The shell includes an n-type dopant.

87. The photovoltaic solar cell device of claim 86, wherein: The n-type dopant includes nitrogen.

88. The photovoltaic solar cell device of claim 87, wherein: The shell includes an amount of n-type dopant sufficient to reduce a work function of the graphene material of the shell by at least 0.5 V.

89. The photovoltaic solar cell device according to any one of claims 62 to 64, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G irradiation, the photovoltaic solar cell has an open circuit voltage between 1.5V and 3.6V.

90. The photovoltaic solar cell device according to any one of claims 62 to 64, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G radiation, the photovoltaic solar cell has a power of at least 1 mA / cm 2 short-circuit current density.

91. The photovoltaic solar cell device according to any one of claims 62 to 64, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G illumination, the photovoltaic solar cell has an open circuit voltage between 2.5V and 3.6V.

92. A method of forming a solar cell, comprising: providing a lower copper foil having a top surface and a bottom surface; providing a zinc foil having a top surface and a bottom surface, the bottom surface of the zinc foil being in contact with the top surface of the copper foil throughout at least a portion of the bottom surface area of ​​the zinc foil to form a foil substrate; forming a plurality of nanowire cores on a top surface of the zinc foil using a hydrothermal synthesis process, the nanowire cores comprising zinc oxide, wherein at least a majority of the nanowire cores are substantially aligned with each other and extend generally perpendicular to the zinc foil and are electrically connected to the foil substrate at first ends of the nanowire cores, the hydrothermal synthesis process forming a substantially continuous coating of zinc oxide between the zinc oxide nanowire cores; treating the nanowire core in a post-growth annealing process to reduce structural defects at the surface of the nanowire core; and then depositing a graphene material on at least a portion of the nanowire core to form a plurality of shells, wherein the graphene material comprises reduced graphene oxide; Wherein, a second conductive electrode is connected to the plurality of shells at a second end of the nanowire core and comprises at least one metal that effectively reduces the work function of graphene.

93. The method of claim 92, wherein: A substantially continuous coating of a non-conductive material is formed on the foil substrate, the coating comprising zinc oxide.

94. The method of claim 92 or 93, wherein: Each reduced graphene oxide shell of the plurality of shells is conformally disposed around a majority of a corresponding nanowire core.

95. The method according to any one of claims 92 to 93, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G illumination, the solar cell has an open circuit voltage between 1.5V and 3.6V.

96. The method of any one of claims 92 to 93, wherein: The foil substrate also includes at least one of titanium, brass, or steel.

97. The method of any one of claims 92 to 93, wherein: The foil substrate consists essentially of zinc.

98. The method of any one of claims 92 to 93, wherein: The plurality of nanowire cores include surface annealed nanowire cores.

99. The method of any one of claims 92 to 93, further comprising: A first conductive electrode is formed that is electrically connected to the foil substrate, wherein the first conductive electrode is not electrically connected to the reduced graphene oxide shell at the first end of the nanowire core, and the second conductive electrode is not electrically connected to the nanowire core via the reduced graphene shell.

100. The method of any one of claims 92 to 93, wherein: The plurality of shells comprises, at least in a majority, two to ten layers of reduced graphene oxide.

101. The method of any one of claims 92 to 93, wherein: The plurality of shells comprises, at least in a majority, two to five layers of reduced graphene oxide.

102. The method of any one of claims 92 to 93, wherein: The plurality of shells include, at least over a majority portion, a layer of graphene.

103. The method of any one of claims 92 to 93, wherein: The plurality of shells are arranged such that their longitudinal axes are oriented at least substantially parallel to one another.

104. The method of any one of claims 92 to 93, wherein: The plurality of shells have a length ranging from 5 microns to 25 microns.

105. The method of any one of claims 92 to 93, wherein: A diameter of a nanowire core in the plurality of nanowire cores does not exceed 500 nanometers.

106. The method of any one of claims 92 to 93, wherein: The plurality of shells are characterized by an aspect ratio of 10 to 250.

107. The method of any one of claims 92 to 93, wherein: The plurality of shells is characterized by a spatial density of 10% to 80%.

108. The method of any one of claims 92 to 93, wherein: The nanowire core includes a dopant along at least a portion of its longitudinal surface.

109. The method of claim 108, wherein: The dopant includes at least one of aluminum, indium, chlorine, and gallium.

110. The method of any one of claims 92 to 93, wherein: The reduced graphene shell includes an n-type dopant.

111. The method according to claim 110, wherein: The n-type dopant includes nitrogen.

112. The method according to claim 111, wherein: The n-type dopant is included in the plurality of shells in an amount effective to lower a work function of the reduced graphene oxide by at least 0.5 V.

113. The method of any one of claims 92 to 93, wherein: The second conductive electrode is at least partially transparent to sunlight.

114. The method of claim 113, wherein: The second conductive electrode is a conductive inorganic material.

115. The method of claim 113, wherein: The second conductive electrode is a conductive organic material.

116. The method of claim 114, wherein: The second conductive electrode includes at least one of indium tin oxide or graphene.

117. The method of claim 114, wherein: The second conductive electrode includes reduced graphene oxide.

118. The method of any one of claims 92 to 93, wherein: A substance effective to reduce the work function of the reduced graphene oxide is in contact with the reduced graphene oxide shell.

119. The method of claim 118, wherein: When using 1KW / m 2 When irradiated with AM 1.5G radiation, the solar cell has a current of at least 1 mA / cm 2 short-circuit current density.

120. The method of claim 119, wherein: The at least one metal effective to reduce the work function of the reduced graphene oxide includes one or more of silver, aluminum, and copper.

121. The method of claim 119, wherein: The second conductive electrode is at least partially transparent to sunlight and includes particles of at least one metal effective to reduce a work function of reduced graphene oxide.

122. The method of claim 121, wherein: The material forming the second conductive electrode is interspersed between the nanowire cores.

123. The method of claim 121, wherein: The second conductive electrode includes indium tin oxide containing silver particles.

124. A photovoltaic solar cell device comprising at least one solar cell, the at least one solar cell being prepared by a method comprising the steps of: providing a foil substrate; A plurality of nanowire cores are formed on the foil substrate using a hydrothermal synthesis process, wherein the nanowire cores comprise zinc oxide, At least a majority of the nanowire cores are substantially aligned with each other and extend generally perpendicular to the foil substrate and are electrically connected to the foil substrate at first ends of the nanowire cores, the hydrothermal synthesis process forming a substantially continuous coating of non-conductive material on the foil substrate between the zinc oxide nanowire cores; Surrounding multiple zinc oxide nanowire cores with graphene oxide; forming a plurality of nanowire core / shell structures by maintaining the zinc oxide nanowire core and graphene oxide under conditions sufficient to thermally reduce at least some of the graphene oxide to form a plurality of shells, each shell comprising reduced graphene oxide and conformally disposed about a portion of a respective nanowire core to form a photovoltaic junction; forming a first conductive electrode electrically connected to the foil substrate and providing a first electrical path to facilitate movement of electrons away from the nanowire core; as well as forming a second conductive electrode connected to the reduced graphene oxide shell at a second end of the nanowire core / shell structure and providing a second electrical path to facilitate movement of positive charge away from the reduced graphene oxide shell, Wherein, the second conductive electrode includes at least one metal that effectively reduces the work function of the reduced graphene oxide.

125. The photovoltaic solar cell device of claim 124, wherein: The substantially continuous coating of non-conductive material comprises zinc oxide.

126. The photovoltaic solar cell device of claim 124 or 125, wherein: Each reduced graphene oxide shell of the plurality of shells is conformally disposed around a majority of a corresponding nanowire core.

127. The photovoltaic solar cell device according to any one of claims 124 to 125, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G irradiation, the photovoltaic solar cell has an open circuit voltage between 1.5V and 3.6V.

128. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The foil substrate includes at least one of zinc, titanium, brass, steel, or copper.

129. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The foil substrate consists essentially of zinc.

130. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: Thermally reducing graphene oxide to reduced graphene oxide is performed in an atmosphere comprising at least 10% hydrogen.

131. The photovoltaic solar cell device of claim 130, wherein: Thermal reduction of graphene oxide to reduced graphene oxide is performed at a temperature between 250°C and 350°C.

132. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: Before the step of surrounding the plurality of zinc oxide nanowire cores with graphene oxide, a post-growth annealing process is performed on the plurality of nanowire cores to reduce structural defects at the surfaces of the nanowire cores.

133. The photovoltaic solar cell device of claim 132, wherein: The post-growth annealing process includes heating the zinc oxide nanowires to a temperature between 350° C. and 400° C. for at least 4 hours in an atmosphere of at least 10% oxygen.

134. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The step of surrounding the plurality of zinc oxide nanowire cores with graphene oxide includes a coating technique.

135. The photovoltaic solar cell device of claim 134, wherein: The coating technique is at least one of drop coating, dip coating or spin coating.

136. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The first conductive electrode is not electrically connected to the reduced graphene oxide shell at the first end of the core, and the second conductive electrode is not electrically connected to the nanowire core via the reduced graphene shell.

137. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The shell comprises, at least in large part, two to five layers of reduced graphene oxide.

138. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The plurality of nanowire core / shell structures are arranged such that their longitudinal axes are oriented at least substantially parallel to one another.

139. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The length of the nanowire core / shell structures in the plurality of nanowire core / shell structures is in a range of 5 microns to 25 microns.

140. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: A diameter of a nanowire core in the plurality of nanowire cores does not exceed 500 nanometers.

141. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The plurality of nanowire core / shell structures are characterized by an aspect ratio of 10 to 250.

142. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The plurality of nanowire core / shell structures are characterized by a spatial density of 10% to 80%.

143. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The nanowire core includes a dopant along at least a portion of its longitudinal surface.

144. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The reduced graphene oxide shell includes an n-type dopant.

145. The photovoltaic solar cell device of claim 144, wherein: The n-type dopant includes nitrogen.

146. The photovoltaic solar cell device of claim 144, wherein: The n-type dopant is included in the shell in an amount sufficient to lower a work function of the reduced graphene oxide by at least 0.5 V.

147. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The second conductive electrode is at least partially transparent to sunlight.

148. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The second conductive electrode is a conductive inorganic material.

149. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The second conductive electrode is a conductive organic material.

150. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The second conductive electrode includes at least one of indium tin oxide or graphene.

151. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: The second conductive electrode includes reduced graphene oxide.

152. The photovoltaic solar cell device of any one of claims 124 to 125, wherein: A substance effective to reduce the work function of the reduced graphene oxide is placed in contact with the reduced graphene oxide shell.

153. The photovoltaic solar cell device of claim 152, wherein: When using 1KW / m 2 When irradiated with AM 1.5G radiation, the photovoltaic solar cell has a power of at least 1 mA / cm 2 short-circuit current density.

154. The photovoltaic solar cell device of claim 153, wherein: The at least one metal effective to reduce the work function of the reduced graphene oxide includes one or more of silver, aluminum, and copper.

155. The photovoltaic solar cell device of claim 153, wherein: The second conductive electrode is at least partially transparent to sunlight and includes particles of at least one metal effective to reduce a work function of reduced graphene oxide.

156. The photovoltaic solar cell device of claim 155, wherein: The material forming the second conductive electrode is interspersed between the nanowire cores.

157. The photovoltaic solar cell device of claim 156, wherein: The second conductive electrode is indium tin oxide containing silver particles.

158. The photovoltaic solar cell device of claim 157, wherein: The second conductive electrode is formed by drop coating, spray coating or spin coating.

159. A photovoltaic solar cell device comprising: Foil substrate; a plurality of nanowire cores on the foil substrate, the nanowire cores comprising zinc oxide, wherein at least a majority of the nanowire cores are substantially aligned with each other and extend generally perpendicular to the foil substrate and are electrically connected to the foil substrate at first ends of the nanowire cores; a substantially continuous coating of a non-conductive material on the foil substrate between the zinc oxide nanowire cores; a plurality of reduced graphene oxide shells, each shell comprising reduced graphene oxide and each shell being conformally disposed around a portion of a corresponding nanowire core to form a plurality of nanowire core / shell structures; a first conductive electrode electrically connected to the foil substrate and providing a first electrical path to facilitate movement of electrons away from the nanowire core; and a second conductive electrode connected to the reduced graphene oxide shell at a second end of the nanowire core / shell structure and providing a second electrical path to facilitate movement of positive charge away from the reduced graphene oxide shell, Wherein, the second conductive electrode includes at least one metal that effectively reduces the work function of the reduced graphene oxide.

160. The photovoltaic solar cell device of claim 159, wherein: The substantially continuous coating of non-conductive material on the foil substrate comprises zinc oxide.

161. The photovoltaic solar cell device of claim 159 or 160, wherein: Each reduced graphene oxide shell of the plurality of shells is conformally disposed around a majority of a corresponding nanowire core.

162. The photovoltaic solar cell device according to any one of claims 159 to 160, characterized in that When using 1KW / m 2 When irradiated with AM 1.5G radiation, the photovoltaic solar cell has an open circuit voltage between 1.5V and V.

163. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The foil substrate includes at least one of zinc, titanium, brass, steel, or copper.

164. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The foil substrate consists essentially of zinc.

165. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The plurality of nanowire cores include surface annealed nanowire cores.

166. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The first conductive electrode is not electrically connected to the reduced graphene oxide shell at the first end of the nanowire core, and the second conductive electrode is not electrically connected to the nanowire core via the reduced graphene shell.

167. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The shell comprises, at least in large part, two to ten layers of reduced graphene oxide.

168. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The shell comprises, at least in large part, two to five layers of reduced graphene oxide.

169. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The plurality of nanowire core / shell structures are arranged such that their longitudinal axes are oriented at least substantially parallel to one another.

170. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The length of the nanowire core / shell structures in the plurality of nanowire core / shell structures is in a range of 5 microns to 25 microns.

171. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: A diameter of a nanowire core in the plurality of nanowire cores does not exceed 500 nanometers.

172. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The plurality of nanowire core / shell structures are characterized by an aspect ratio of 10 to 250.

173. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The plurality of nanowire core / shell structures are characterized by a spatial density of 10% to 80%.

174. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The nanowire core includes a dopant along at least a portion of its longitudinal surface.

175. The photovoltaic solar cell device of claim 174, wherein: The dopant includes at least one of aluminum, indium, chlorine, and gallium.

176. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The reduced graphene shell includes an n-type dopant.

177. The photovoltaic solar cell device of claim 176, wherein: The n-type dopant includes nitrogen.

178. The photovoltaic solar cell device of claim 177, wherein: The n-type dopant is included in the shell in an amount effective to lower a work function of the reduced graphene oxide by at least 0.5 V.

179. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: The second conductive electrode is at least partially transparent to sunlight.

180. The photovoltaic solar cell device of claim 179, wherein: The second conductive electrode is a conductive inorganic material.

181. The photovoltaic solar cell device of claim 179, wherein: The second conductive electrode is a conductive organic material.

182. The photovoltaic solar cell device of claim 180, wherein: The second conductive electrode includes at least one of indium tin oxide or graphene.

183. The photovoltaic solar cell device of claim 180, wherein: The second conductive electrode includes reduced graphene oxide.

184. The photovoltaic solar cell device of any one of claims 159 to 160, wherein: A substance effective to reduce the work function of the reduced graphene oxide is in contact with the reduced graphene oxide shell.

185. The photovoltaic solar cell device of claim 184, wherein: When using 1KW / m 2 When irradiated with AM 1.5G radiation, the photovoltaic solar cell has a power of at least 1 mA / cm 2 short-circuit current density.

186. The photovoltaic solar cell device of claim 185, wherein: The at least one metal effective to reduce the work function of the reduced graphene oxide includes one or more of silver, aluminum, and copper.

187. The photovoltaic solar cell device of claim 185, wherein: The second conductive electrode is at least partially transparent to sunlight and includes particles of at least one metal effective to reduce a work function of reduced graphene oxide.

188. The photovoltaic solar cell device of claim 187, wherein: The material forming the second conductive electrode is interspersed between the nanowire cores.

189. The photovoltaic solar cell device of claim 187, wherein: The second conductive electrode includes indium tin oxide containing silver particles.

Citation Information

Patent Citations

  • Apparatus pertaining to a core of wide band-gap material having a graphene shell

    US8586999B1

  • Apparatus pertaining to the co-generation conversion of light into electricity

    US8829331B2

  • Apparatus pertaining to solar cells having nanowire titanium oxide cores and graphene exteriors and the co-generation conversion of light into electricity using such solar cells

    US9040395B2

  • Large area deposition of graphene on substrates, and products including the same

    CN102741164A

  • Photovoltaic cell and method of fabricating the same

    CN105637656A